Invasive Pleomorphic Lobular Carcinoma of The Male Breast: A Rare Diagnosis with Radiologic-Pathologic Correlation - Costa, Marta (2022)
Male breast cancer is a rare disease, representing approximately 1% of all breast cancers, but its incidence appears to be increasing over the years. As normal male breast does not develop acini and lobules, lobular carcinoma is very rare, accounting for 1% - 2% of all cases of male breast cancer. Pleomorphic lobular carcinoma is an aggressive variant of invasive lobular carcinoma with only six cases of male breast reported in the literature until now, and none with associated Paget’s disease. We report a case of an invasive pleomorphic lobular carcinoma with axillary lymph node involvement and associated Paget’s disease in a high-risk man. Low awareness among men and a lack of a screening program often lead to a late diagnosis of male breast cancer, and consequently, at a later stages of disease, with lower survival rates compared to women. Early diagnosis is essential in order to improve patient outcomes and achieve better survival rates in men.